Implementation of the Value for Money Concept in Measuring Financial Performance at the Library and Archives Service of West Kalimantan Province - Lestari, Dewi Ayu; Aswat, Ibnu; Yantiana, Nella (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the financial performance of the Library and Archives Office of West Kalimantan Province using the concept of Value for Money (VFM). The VFM concept is important in public financial management because it emphasizes three main aspects: economy, efficiency, and effectiveness. This research uses a qualitative approach and quantitative descriptive data analysis, with primary data obtained through interviews and observations, as well as secondary data in the form of Budget Realization Reports (LRA). The results of the analysis show that in terms of economic ratios, the Department has made expenditures quite economically. In terms of efficiency ratios, the Service is very efficient in the use of resources. However, in terms of effectiveness ratio, the Department has not been fully effective in achieving the expected goals. Although budget management is done well in terms of economy and efficiency, there is still room for improvement in terms of effectiveness.